1999
DOI: 10.1093/emboj/18.19.5359
|View full text |Cite
|
Sign up to set email alerts
|

The promoter of a novel human papillomavirus (HPV77) associated with skin cancer displays UV responsiveness, which is mediated through a consensus p53 binding sequence

Abstract: An aetiological role has been proposed for human papillomavirus (HPV) in skin carcinogenesis within the immunosuppressed patient population. To examine this possibility, we have focused on an HPV type that, to date, has been identified only in the cutaneous lesions of renal transplant recipients despite a high degree of sequence homology with other HPVs commonly found in warts in the general population. We report that the non-coding region of this virus, HPV type 77, contains a consensus binding site for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 44 publications
0
49
0
2
Order By: Relevance
“…As HPV 77 is found in tumours of immunocompromised patients, this activity of HPV 77 could, at least in part, explain how p53-induced apoptosis at sun-exposed sites may be averted in absence of p53 degradation. We previously reported that the HPV 77 URR (upstream regulatory region), which controls the expression of the E6 and E7 genes, contains a p53-responsive element and can be transcriptionally activated by p53 (Purdie et al, 1999). Therefore in HPV 77 cells, resistance to apoptosis could facilitate proliferation of infected cells and further the tumorigenic process by increasing the expression of E6 or other viral proteins.…”
Section: Deregulation Of Transactivation Proapoptotic Genes By Hpv 77 E6mentioning
confidence: 99%
“…As HPV 77 is found in tumours of immunocompromised patients, this activity of HPV 77 could, at least in part, explain how p53-induced apoptosis at sun-exposed sites may be averted in absence of p53 degradation. We previously reported that the HPV 77 URR (upstream regulatory region), which controls the expression of the E6 and E7 genes, contains a p53-responsive element and can be transcriptionally activated by p53 (Purdie et al, 1999). Therefore in HPV 77 cells, resistance to apoptosis could facilitate proliferation of infected cells and further the tumorigenic process by increasing the expression of E6 or other viral proteins.…”
Section: Deregulation Of Transactivation Proapoptotic Genes By Hpv 77 E6mentioning
confidence: 99%
“…The mechanism of degradation, shared with anogenital HPVs, indicates that the cutaneous E6 proteins are able to discriminate between p53 and Bak as targets. This is critical to HPV77 since it utilizes transcriptionally active p53 to increase viral gene transcription (Purdie et al 1999). Analysis of clonal p53 mutant cell patches in human skin demonstrated that they had little or no precancerous potential (Jonason et al 1996;Ren et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more HPV types have been found in actinic keratosis and SCC skin lesions than in normal skin (Alotaibi et al, 2006), and a greater variety of HPV types have also been found in immunosuppressed individuals than in immunocompetent individuals (Harwood et al, 2004). Both SCC and BCC develop mostly on sun-exposed sites (Frost & Green, 1994), and some specific types of HPV, including HPV-5, HPV-8, HPV-20 and HPV-77, have been shown to be activated by UV radiation (Akgül et al, 2005;Massimi et al, 2008;Michel et al, 2006;Purdie et al, 1999;Storey et al, 1998). Evidence of UV-induced E6/E7 oncogenicity and transcriptional activity of E6/E7 oncogenes in NMSC has been found (Al Moustafa et al, 2004;Dang et al, 2006;Michel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%